Performance Arts - Janine Sprünker (Digithum, 2007)
In Catalonia, it is not until the last four years that a growing interest has been seen in the creation of face-to-face exhibitions on the performing heritage. The aim of these exhibitions is to disseminate and preserve the performing heritage for present and future generations to remember this artistic expression and keep it in the collective memory. Museologists and exhibition organisers have to be able to submerge themselves in the imagination from which the performing heritage comes in order to be able to interpret it. In this sense, we can use the research methods and techniques offered to us by ethnographic methodology, which is used at the same time by the creative teams of performance production companies. Wen interpreting the performing heritage, we have to formulate a face-to-face communicative framework and establish a scenario, which must also be accessible online, taking into consideration that we have to communicate and disseminate the knowledge that the heritage has to a broad range of audiences. Despite this, as well as offering contexts in different modes, online and face-to-face, with interpretative keys, i.e. resources and mechanisms that give out and make understandable the messages, today we have to make a diverse public participate in an alien reality.